8-11 Pemberton Square, ca. 1885 - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking northwest of the multi-story brick buildings at (left to right) 11, 10, 9 and 8 Pemberton Square. A policeman is standing between 8 and 9 Pemberton Square. A horse-drawn carriage is waiting in front of 8 Pemberton Square. 6 x 8 1/8 Photographs